2017
DOI: 10.1136/bmjoq-2017-000146
|View full text |Cite
|
Sign up to set email alerts
|

Using ‘Active Signposting’ to streamline general practitioner workload in two London-based practices

Abstract: General practice is at the forefront of the National Health Service, but is currently being overwhelmed by ever-increasing patient demand and financial constraints. Telephone consultations (TCs) have been used as a method to ease pressure on general practice. Many of these consultations are booked with general practioners (GPs), despite occasions when the patient could have either been signposted to self-help or offered an alternative service. This quality improvement project (QIP) aimed to evaluate the nature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…With time constraints being common in healthcare, minimal disruption has been reported to be important in the implementation of clinical behaviours [47]. Active signposting has been shown to be effective in the context of reducing the amount of inappropriate GP consultations by triaging patients to a more appropriate healthcare professional [48]; and it is recommended in the UK NHS Year of Care initiative for managing long term conditions [49]. During the workshops, previous occurrences of indirect referral were described as acceptable by dental professionals in the case of suspected diabetes; and medical professionals suggested that indirect referral from a variety of sources was not only commonplace, but actually preferred over a letter or a telephone call.…”
Section: Discussionmentioning
confidence: 99%
“…With time constraints being common in healthcare, minimal disruption has been reported to be important in the implementation of clinical behaviours [47]. Active signposting has been shown to be effective in the context of reducing the amount of inappropriate GP consultations by triaging patients to a more appropriate healthcare professional [48]; and it is recommended in the UK NHS Year of Care initiative for managing long term conditions [49]. During the workshops, previous occurrences of indirect referral were described as acceptable by dental professionals in the case of suspected diabetes; and medical professionals suggested that indirect referral from a variety of sources was not only commonplace, but actually preferred over a letter or a telephone call.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also highlighted the importance of training and skills in CN and SPLW roles. The success of a CN intervention evaluated across two practices (8) was in uenced by staff training in the use of the CN protocols; a realist review (17) identi ed that su ciently trained and knowledgeable link workers enabled the successful transition of patients between services.…”
Section: Summary Of Ndings and Comparison With Existing Literaturementioning
confidence: 99%
“…CN staff had grave concerns about failing to recognise serious health issues when patients presented for help, and risking patient safety by inappropriately diverting them away from GP appointments. Although it has been highlighted previously that any signposting should privilege patient preference and safety, it is also evident that even experienced clinicians vary in their assessment of what constitutes a potentially avoidable appointment request (8). This raises concerns about the advisability of CN receptionists managing risk in the unpredictable setting of general practice, where even quali ed and experienced clinicians must develop risk-management skills over time (31).…”
Section: Summary Of Ndings and Comparison With Existing Literaturementioning
confidence: 99%
“…Whether the CN role is meeting these expressed aims is currently unclear. One small-scale peer reviewed study [8] and two case studies [9,10] suggest that care navigation can reduce the number of 'potentially avoidable' [8] or 'inappropriate' [9] GP appointments carried out by practices. For example, over a 7-month period, care navigation was calculated to have saved 1,685 GP appointments across an area in the North of England [10].…”
Section: Introductionmentioning
confidence: 99%